Pengalaman dan persepsi atlet putri elit pada siklus menstruasi terhadap performa dan prestasi dalam kompetisi olahraga di jawa tengah - Aprila Sintya Safitri; Prisca Widiawati; Muhammad Putra Ramadhan (Bravo's: Jurnal Program Studi Pendidikan Jasmani dan Kesehatan, 2025)
Coaches need to consider various competencies such as conditioning, training program skills and tactics, when planning sessions, despite the rare impact of the menstrual cycle on the effectiveness of competitive training performance of female athletes in Central Java. The impact of the menstrual cycle of female athletes, the training strategies used by female athletes to minimize the impact of training programs that provide obstacles to large interactions with coaches require consideration. This research aims to determine the experiences of elite female athletes regarding the menstrual cycle while competing in Central Java and to understand female athletes' perceptions of the influence of the menstrual cycle on performance and achievement in sports competitions. A questionnaire containing 36 items was developed. Univariate analysis was used to analyze the data. Thirty-six valid responses from Central Javanese female athletes aged 14 to 27 years, with an average age of 19 years, were received. Menstrual pain (72.3%) and pre-menstrual symptoms (72.2%). Contraceptive use by 2.8% of female athletes. Those reporting heavy menstrual bleeding (25%). Most athletes reported that neither they nor their coaches changed training due to the menstrual cycle (61.1%). Most athletes (50%) discussed with female coaches only. Given the perceived impact on performance and potential risks of contraceptive use during pregnancy, teens, coaches, and athletes need to have a more open dialogue around the menstrual cycle